Progression of an Invasive ACTH Pituitary Macroadenoma with Cushing’s Disease to Pituitary Carcinoma - Clarissa Groberio Borba; Rafael Loch Batista; Nina Rosa de Castro Musolino; Vanielle Carvalho Machado; Ana Elisa Evangelista Alcantara; Gilberto Ochman da Silva; Valter Angelo Sperling Cescato; Malebranche Berardo Carneiro da Cunha Neto (Case Reports in Oncological Medicine)
Pituitary carcinomas are very rare tumors that in most cases produce prolactin and adrenocorticotropic hormone (ACTH). It is a challenge to diagnosis of a pituitary carcinoma before disclosed symptomatic metastasis. We report the case of a female patient with Cushing’s disease who underwent three transsphenoidal surgeries, with pathological findings of common ACTH pituitary adenoma including Ki-67 expression <3%. She achieved hypocortisolism after the 3rd surgery although ACTH levels remained slightly elevated. The patient returned some time later with fast worsening of hypercortisolism. Magnetic resonance imaging showed clivus invasion, which led to a fourth surgery and radiation. This time, immunohistochemistry revealed strong Ki-67 (10% to 15%) and p53 expression. Liver and lumbar spine metastases were found on workup. The patient died after few months due to lung infection. Pituitary carcinomas are rare, and the transformation of an ACTH-secreting pituitary adenoma into a carcinoma is exceptional. The difficulty of defining markers for the diagnosis of carcinoma, before metastasis diagnosis, in order to change the management of the disease, is a challenge.